2015
DOI: 10.1038/srep10936
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms linking metabolism of Helicobacter pylori to 18O and 13C-isotopes of human breath CO2

Abstract: The gastric pathogen Helicobacter pylori utilize glucose during metabolism, but the underlying mechanisms linking to oxygen-18 (18O) and carbon-13 (13C)-isotopic fractionations of breath CO2 during glucose metabolism are poorly understood. Using the excretion dynamics of 18O/16O and 13C/12C-isotope ratios of breath CO2, we found that individuals with Helicobacter pylori infections exhibited significantly higher isotopic enrichments of 18O in breath CO2 during the 2h-glucose metabolism regardless of the isotopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…In addition, a growing body of evidence suggests that the effects of H. pylori may also be relevant to several other extragastric diseases including idiopathic thrombocytopenic purpura, cardiovascular disease, anemia, diabetes, and insulin resistance [11,12]. In recent years, a few studies have reported that the oxygen-18 ( 18 O) isotopes in exhaled CO 2 are also a biomarker related to H. pylori because of the rapid exchange of the 16 O in 12 C 16 O 2 and 18 O in H 2 18 O in response to periplasmic α-carbonic anhydrase activity [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, a growing body of evidence suggests that the effects of H. pylori may also be relevant to several other extragastric diseases including idiopathic thrombocytopenic purpura, cardiovascular disease, anemia, diabetes, and insulin resistance [11,12]. In recent years, a few studies have reported that the oxygen-18 ( 18 O) isotopes in exhaled CO 2 are also a biomarker related to H. pylori because of the rapid exchange of the 16 O in 12 C 16 O 2 and 18 O in H 2 18 O in response to periplasmic α-carbonic anhydrase activity [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For gas identification and quantification, there are significant advantages to laser absorption spectroscopy, such as high sensitivity, high selectivity, fast response, and realtime online analysis [16][17][18][19][20]. Many laser absorption spectroscopy based sensors have been developed for monitoring the human breath CO 2 isotopes in recent years, especially for 13 C. Generally, the δ value has been used to describe the relative deviation of the sample isotope ratio from the standard reference value (e.g., the standard abundance in Vienna Peedee Belemnite (VPDB)). Crosson et al constructed a cavity ring-down spectrometer using a three-mirror high-finesse ring-down cavity, and demonstrated the ability to obtain δ 13 C in breath samples [21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By taking a small amount of 13 C-labeled pills, a suspected H. pylori patient will exhibit enrichment of 13 CO 2 in the exhaled gas, which is usually reported as the delta over baseline (DOB) value relative to a standard [3][4] . Recently, the 18 Oisotope of CO 2 in exhaled gas was also demonstrated as a potential molecular biomarker to track the pathogenesis of H. pylori 5 distinctively. A δ DOB 13 C ≥2.0‰ or δ DOB 18 O ≥1.92‰ is strongly relevant with the infection of H. pylori in the human stomach [6][7] .…”
mentioning
confidence: 99%